Analysis Of Nutrient Levels In Lais Fish (Kryptoterus Sp) As A Potential Local Food Source To Prevent Stunting - Khotimah, Siti; Hanis Kusumawati Rahayu; Maina, Annin Dya (Universitas Muhammadiyah Kalimantan Timur, 2025)
Stunting indicates impaired growth in children under the age of five due to chronic malnutrition, especially during the first 1000 days of life. The existence of complementary feeding can complement the nutritional needs of children. Complementary foods are transitional foods from breast milk to foods consumed by the family slowly. Fish contains vitamins and proteins that are more abundant than beef or goat. The potential of fisheries in East Kalimantan Province is quite high, so people can easily get animal protein sources such as fish. There are various types of fish caught by fishermen in the Mahakam River. Three types of local fish that are often caught by fishermen are Cork Fish (Channa Striata), Lais Fish (Cryptoterus sp.) and Betok Fish (Anabas testudineus). This study aims to determine the content in lais fish (kryptoterus sp) as a potential local food source to prevent stunting. This research is an experimental study with an Intac-group comparison approach. Simple random sampling technique. Based on the results of the study, the percentage of lais fish meat content for 24-hour treatment is water (96.4%), protein (2.16%), fat (2.45%), carbohydrates (1.28%) and ash (0.27%). The 48-hour treatment contained water (94.1%), protein (13.31%), fat (3.7%), carbohydrates (11.87%) and ash (0.76%). The 72-hour treatment was water content (82.14%), protein (22.56%), fat (1.89%), carbohydrates (8.78%) and ash (2.19%).